Edge folding glue as well as preparation method and application thereof
By introducing epoxy resin toughening agent and rubber toughening agent into the folding glue, combined with the compounding technology of specific fillers and additives, the existing folding glue is solved, and the car body is realized The high viscosity and good adhesiveness of the connection parts improve the structural bonding and sealing performance of the car body.
Patent Information
- Application Number
- CN202411727827.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-14
AI Technical Summary
The existing epoxy resin-based edging glue still has room to improve its adhesiveness, especially in the use environment of automobile body, which requires better adhesiveness and sealing.
By introducing epoxy resin toughening agent and rubber toughening agent into the preparation raw material of the edging glue, and combining specific types of fillers and additives, the edging glue has high viscosity at room temperature and It has good adhesion and sealing after baking and curing.
It achieves high viscosity and good adhesion in the connection parts of the car body, and is suitable for use in doors, engine covers, suitcase covers and other parts, improving the structural bonding and sealing performance of the car body, and extending the body life.
Smart Images

Figure BDA0005159621710000061 
Figure BDA0005159621710000062 
Figure BDA0005159621710000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and relates to an edge-folding adhesive and a preparation method and application thereof, and in particular to an edge-folding adhesive for automobiles and a preparation method and application thereof. Background Art
[0002] With the improvement of people's living standards, cars have become an indispensable means of transportation for people in their daily lives, and the appearance of cars has become more and more the focus of attention of young buyers. The inner and outer panels of car doors, engine hoods, and trunk lids need to be bonded with folding glue after hemming. This can not only enhance structural bonding, seal the car body, improve the safety performance of the car body collision and extend the life of the car body, but also eliminate pits and ensure the smoothness and beauty of the car body by replacing welding with bonding. If the product uses galvanized steel plates, the welding connection method will also damage the zinc layer around the welding part, resulting in reduced anti-corrosion performance of the product. Therefore, replacing welding with bonding can also effectively solve the rust caused by the destruction of the zinc layer. At the same time, it can also prevent the premature rust of the bonding part due to the inability to paint.
[0003] The existing hemming adhesives mainly include epoxy resin, polyvinyl chloride, rubber, etc. Among them, epoxy resin hemming adhesive has no corrosive gas release and good corrosion resistance, so it is the main type of hemming adhesive, but the adhesion of the existing epoxy resin hemming adhesive needs to be further improved.
[0004] Therefore, it is desirable in the art to develop a hemming adhesive for automobile bodies that has good adhesion. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a hem glue and a preparation method and application thereof, and specifically to provide a hem glue for automobiles and a preparation method and application thereof.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a hemming adhesive, wherein the raw materials for preparing the hemming adhesive include a toughening agent, an epoxy resin, a filler, and an additive;
[0008] The toughening agent includes epoxy resin toughening agent and rubber toughening agent.
[0009] The raw materials for preparing the hemming glue provided by the present invention include a toughening agent, an epoxy resin, a filler, and an auxiliary agent. Through the coordinated coordination of the various components, especially the introduction of a specific type of toughening agent for compounding, the hemming glue has high viscosity at room temperature, and after baking and curing, has good adhesion and sealing properties, and is suitable for use in the connection parts such as car doors, engine hoods, trunk lids, roof beams, and inner and outer panels.
[0010] Preferably, the raw materials for preparing the hemming glue include, by weight, 10 to 25 parts of epoxy resin toughener, 8 to 20 parts of rubber toughener, 10 to 18 parts of epoxy resin, 30 to 40 parts of filler, and 16 to 41 parts of additives.
[0011] Preferably, the raw materials for preparing the hemming glue are measured in parts by weight, and the amount of the epoxy resin toughening agent used can be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 25 parts, etc.
[0012] Preferably, the raw materials for preparing the hemming glue are measured by weight, and the amount of the rubber toughening agent used can be 8 parts, 9 parts, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, etc.
[0013] Preferably, the raw materials for preparing the hemming glue are measured in parts by weight, and the amount of epoxy resin used can be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, etc.
[0014] Preferably, the raw materials for preparing the hemming glue are measured by weight, and the amount of filler used can be 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, etc.
[0015] Preferably, the raw materials for preparing the hemming glue are measured by weight, and the amount of the auxiliary agent used can be 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, 41 parts, etc.
[0016] Preferably, the epoxy resin includes any one of bisphenol A epoxy resin, novolac epoxy resin, alicyclic epoxy resin, and glycidylamine epoxy resin, or a combination of at least two thereof.
[0017] Preferably, the filler comprises any one of silicon micropowder, heavy calcium carbonate, nano-active calcium carbonate, mica powder, barium sulfate, talcum powder, or a combination of at least two thereof, preferably silicon micropowder and nano-active calcium carbonate.
[0018] As a preferred technical solution of the present invention, the combination of silicon micropowder and nano-activated calcium carbonate can make the hemming glue colloid have better acid and alkali resistance stability and reinforcement effect. If only silicon micropowder is added, the surface of the hemming glue colloid will be rough. If only nano-activated calcium carbonate is added, the colloid stability will decrease and the cost will increase.
[0019] Preferably, the mass ratio of the silicon micropowder to the nano-activated calcium carbonate is (2-4):1, for example, 2.2:1, 2.4:1, 2.6:1, 2.8:1, 3:1, 3.2:1, 3.4:1, 3.6:1, 3.8:1 or 4:1, etc.
[0020] Preferably, the auxiliary agent includes any one of thixotropic agent, flame retardant, curing agent, curing accelerator, water absorbent, diluent, anti-aging agent or a combination of at least two thereof. By adding the above-mentioned auxiliary agents, the hemming glue has the following characteristics: excellent thixotropic property; can be applied by air pump; has good adhesion to automobile cold-rolled steel sheet and galvanized sheet; has excellent anti-aging property in environmental medium, and can protect adherend from corrosion; does not pollute pretreatment, electrophoresis and other tank liquids before curing. The anti-aging agent keeps high aging resistance, the curing agent and curing accelerator are added for the curing of toughening agent and epoxy resin, and the thixotropic agent and diluent are added to make the hemming glue have suitable thixotropy and viscosity, which can meet customer needs.
[0021] Preferably, the auxiliary agent includes 2 to 5 parts of thixotropic agent (for example, 2 parts, 3 parts, 4 parts or 5 parts, etc.), 5 to 8 parts of flame retardant (for example, 5 parts, 6 parts, 7 parts or 8 parts, etc.), 2 to 5 parts of curing agent (for example, 2 parts, 3 parts, 4 parts or 5 parts, etc.), 0.2 to 1 part of curing accelerator (for example, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1 parts, etc.), 2 to 5 parts of water absorbent (for example, 2 parts, 3 parts, 4 parts or 5 parts, etc.), 3 to 8 parts of diluent (for example, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts or 8 parts, etc.), and 0.2 to 1 part of aging resistance agent (for example, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1 parts, etc.).
[0022] Preferably, the thixotropic agent includes any one of carbon black, white carbon black, magnesium carbonate or short fibers, or a combination of at least two thereof.
[0023] Preferably, the flame retardant includes any one of aluminum hydroxide, aluminum oxide, and magnesium hydroxide, or a combination of at least two of them.
[0024] Preferably, the curing agent includes any one of dicyandiamide, 2-methylimidazole, 2-ethyl-4-methylimidazole or 2-phenylimidazole, or a combination of at least two thereof.
[0025] Preferably, the curing accelerator includes any one of an organic urea accelerator, an amine accelerator, and a metal organic salt accelerator, or a combination of at least two of them.
[0026] Preferably, the water absorbing agent comprises calcium oxide.
[0027] Preferably, the diluent comprises an epoxy reactive diluent, including any one of allyl glycidyl ether, alkyl glycidyl ether, and 1,6-hexanediol diglycidyl ether, or a combination of at least two thereof.
[0028] Preferably, the anti-aging agent includes an antioxidant 1010 .
[0029] Preferably, the raw materials for preparing the hemming glue also include 2 to 8 parts of glass beads, such as 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts or 8 parts, etc. The addition of glass beads can improve the problem of glue overflow when the steel plate is hemmed, and the glass beads can play the role of "rivets", thereby obtaining a higher initial strength and improving the problem of steel plate misalignment; and it does not reduce the bonding strength of the hemming glue, and can achieve the effect of controlling the gap degree.
[0030] Preferably, the glass microspheres include hollow glass microspheres and / or solid glass microspheres.
[0031] In a second aspect, the present invention provides a method for preparing the hem glue as described in the first aspect, the preparation method comprising the following steps:
[0032] The toughening agent, epoxy resin, filler and auxiliary agent are mixed, and then vacuum dispersed to obtain the hemming adhesive.
[0033] Preferably, the mixing is performed under the condition of cooling water circulation.
[0034] Preferably, the mixing is carried out in a planetary machine.
[0035] Preferably, the mixing time is 3 to 5 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, etc.
[0036] In a third aspect, the present invention provides a use of the hemming adhesive as described in the first aspect in bonding metal sheets.
[0037] Preferably, the metal sheet includes a cold-rolled steel sheet, an aluminum sheet or a galvanized sheet.
[0038] Compared with the prior art, the present invention has at least the following beneficial effects:
[0039] The raw materials for preparing the hemming glue provided by the present invention include a toughening agent, an epoxy resin, a filler, and an auxiliary agent. Through the coordinated coordination of the various components, especially the introduction of a specific type of toughening agent for compounding, the hemming glue has high viscosity at room temperature, and after baking and curing, has good adhesion and sealing properties, and is suitable for use in the connection parts such as car doors, engine hoods, trunk lids, roof beams, and inner and outer panels. DETAILED DESCRIPTION
[0040] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0041] Unless otherwise specified, some of the raw material information used in the examples and comparative examples of the present invention is as follows:
[0042] Epoxy resin toughening agent: MX154;
[0043] Phenolic resin toughening agent: F10;
[0044] Rubber toughening agent: EZ120;
[0045] Silica powder: B03-1;
[0046] Nano-activated calcium carbonate: CCR;
[0047] Hollow glass microspheres: VS5500;
[0048] Solid glass beads: SF60;
[0049] Urea accelerator: UR300;
[0050] Epoxy resin reactive diluent: AGE.
[0051] Examples 1 to 11, Comparative Examples 1 to 3
[0052] A hemming adhesive, the specific components contained in the raw materials for its preparation are shown in Table 1 and Table 2, and the amount of each component is "parts by weight".
[0053] The preparation method comprises the following steps: under the condition of cooling water circulation, the raw materials are mixed evenly in a high-speed dispersing planetary machine according to the formula, and then vacuumed and stirred for 1 hour to obtain the hemming glue.
[0054] Table 1
[0055]
[0056] Table 2
[0057]
[0058]
[0059] The performance test of the hemming adhesive provided in the embodiment and the comparative example is carried out, and the test method is as follows:
[0060] (1) Storage stability: The sample after the rotational viscosity is measured is placed at a constant temperature of 40°C for 168 hours, then taken out and placed under standard conditions (temperature (23±2)°C, humidity (55±10)%) for 24 hours, and then the rotational viscosity is re-measured and the viscosity change rate is calculated; wherein, the rotational viscosity is measured according to the test method of GB / T 2794, and the unit is mPa·s;
[0061] (2) Sample preparation:
[0062] Shear module sample: Prepare an oil test piece substrate with a size of 100×25×2mm, apply the sample glue on the test piece, the coating area is 25×12.5mm, and the thickness of the glue layer is 0.2mm. Then overlap and overlap another same test piece with it, scrape off the excess sample glue, and then clamp it from both sides with two clips, put it in a high temperature 170℃ oven for 20 minutes, then take it out and place it at room temperature for the following tests;
[0063] T peeling module sample: prepare an oil test piece with a size of 200mm*25mm*1mm, a coating area of 150mm*25mm, and a glue layer thickness of 0.2mm. Then overlap another same test piece with it, scrape off the excess glue, and then clamp it from both sides with two clips. Put it in a high-temperature 170℃ oven and bake it for 20 minutes, then take it out and place it at room temperature for the following tests.
[0064] Shear strength: After the shear module is cured, place it in an environment of (23±2)℃ for 4 hours, and then test the strength according to the method of GB / T 7124;
[0065] Water resistance: After the shear module is cured, it is placed in 40℃ water for 168h, and then placed at (23±2)℃ for 24h to test the shear strength;
[0066] Resistance to moisture and heat aging: After the shear module is cured, it is placed in an aging test chamber at 85°C and 85% RH for 168 hours, and then the shear strength is tested after being placed at (23±2)°C for 24 hours;
[0067] Salt spray resistance: After the shear module is cured, it is placed in a salt spray test chamber with a sodium chloride content of 5% and a temperature of 30°C for 500 hours, and then the shear strength is tested after being placed at (23±2)°C for 24 hours.
[0068] T peel strength (N / mm): After the T peel module is cured, it is placed under standard conditions (temperature (23±2)℃, humidity (55±10)%) for 4 hours, and then the T peel strength is tested according to the method of GB / T 2791.
[0069] The performance test results are shown in Table 3.
[0070] Table 3
[0071]
[0072] It can be seen from Table 3 that the hemming adhesives provided in the embodiments of the present invention have excellent storage stability (viscosity conversion rate is 15.8% to 18.2%), adhesion (shear strength at room temperature is 21.4 to 27.5 MPa, T peel strength is 6.0-7.8 N / mm), water resistance (shear strength after water treatment is 18.2 to 22.9 MPa), resistance to wet and hot aging (shear strength after wet and hot aging is 21.1 to 27.7 MPa) and resistance to salt spray (shear strength after salt spray treatment is 20.7 to 26.9 MPa).
[0073] Compared with Example 1, the storage stability, adhesion, water resistance, moisture and heat aging resistance and salt spray resistance of the hem glue provided in Comparative Example 1 are significantly reduced; the storage stability and T-peel strength of the hem glue provided in Comparative Example 2 are significantly reduced; the storage stability, adhesion, water resistance, moisture and heat aging resistance and salt spray resistance of the hem glue provided in Comparative Example 3 are also significantly reduced.
[0074] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the hemming adhesive and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A hem glue, characterized in that: The raw materials for preparing the hemming adhesive include toughening agent, epoxy resin, filler and auxiliary agent; The toughening agent includes epoxy resin toughening agent and rubber toughening agent.
2. The hem glue according to claim 1, characterized in that: The raw materials for preparing the hemming glue include, by weight, 10 to 25 parts of epoxy resin toughener, 8 to 20 parts of rubber toughener, 10 to 18 parts of epoxy resin, 30 to 40 parts of filler, and 16 to 41 parts of auxiliary agent.
3. The hem glue according to claim 1 or 2, characterized in that: The epoxy resin includes any one of bisphenol A epoxy resin, novolac epoxy resin, alicyclic epoxy resin, and glycidylamine epoxy resin, or a combination of at least two thereof; Preferably, the filler comprises any one of silicon micropowder, heavy calcium carbonate, nano-active calcium carbonate, mica powder, barium sulfate, talcum powder, or a combination of at least two thereof, preferably silicon micropowder and nano-active calcium carbonate.
4. The hem glue according to any one of claims 1 to 3, characterized in that: The auxiliary agent includes any one or a combination of at least two of a thixotropic agent, a flame retardant, a curing agent, a curing accelerator, a water absorbent, a diluent, and an anti-aging agent; Preferably, the auxiliary agent includes 2 to 5 parts of thixotropic agent, 5 to 8 parts of flame retardant, 2 to 5 parts of curing agent, 0.2 to 1 part of curing accelerator, 2 to 5 parts of water absorbent, 3 to 8 parts of diluent, and 0.2 to 1 part of anti-aging agent.
5. The hem glue according to claim 4, characterized in that: The thixotropic agent includes any one of carbon black, white carbon black, magnesium carbonate or short fibers, or a combination of at least two thereof; Preferably, the flame retardant includes any one of aluminum hydroxide, aluminum oxide, and magnesium hydroxide, or a combination of at least two thereof; Preferably, the curing agent includes any one or a combination of at least two of dicyandiamide, 2-methylimidazole, 2-ethyl-4-methylimidazole or 2-phenylimidazole; Preferably, the curing accelerator includes any one of an organic urea accelerator, an amine accelerator, and a metal organic salt accelerator, or a combination of at least two of them.
6. The hem glue according to claim 4 or 5, characterized in that: The water absorbing agent includes calcium oxide; Preferably, the diluent comprises an epoxy reactive diluent, including any one or a combination of at least two of allyl glycidyl ether, alkyl glycidyl ether, and 1,6-hexanediol diglycidyl ether; Preferably, the anti-aging agent includes an antioxidant 1010 .
7. The hem glue according to any one of claims 1 to 6, characterized in that: The raw materials for preparing the hemming glue also include 2 to 8 parts of glass micro beads; Preferably, the glass microspheres include hollow glass microspheres and / or solid glass microspheres.
8. A method for preparing the hem glue according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The toughening agent, epoxy resin, filler and auxiliary agent are mixed, and then vacuum dispersed to obtain the hemming adhesive.
9. The preparation method according to claim 8, characterized in that: The mixing is carried out under the condition of cooling water circulation; Preferably, the mixing is carried out in a planetary machine; Preferably, the mixing time is 3 to 5 hours.
10. Use of the hemming adhesive as claimed in any one of claims 1 to 7 in bonding metal sheets; Preferably, the metal sheet comprises a steel sheet, an aluminum sheet or a galvanized sheet.
Citation Information
Patent Citations
Thermosetting epoxy resin adhesive with characteristics of high flexibility and high-temperature resistance
CN105602501A
Low-temperature-impact-resistant epoxy adhesive composition and preparation method thereof
CN108570302A
Folding-edge glue with high peeling toughness and preparation method thereof
CN108865033A
Photocurable epoxy resin systems
US20160376435A1
Cited By
High-toughness high-temperature curing epoxy resin prepreg for automatic fiber placement and preparation method of high-toughness high-temperature curing epoxy resin prepreg
CN120606583A